Non-lethal sonodynamic therapy facilitates the M1-to-M2 transition in advanced atherosclerotic plaques via activating the ROS–AMPK–mTORC1–autophagy pathway - Yang, Yang (Redox Biol, 2020)
Emerging evidence indicates that macrophage functional polarization is critically involved in the development of atherosclerosis (AS). Here, we examined the role of 5-aminolaevulinic acid (ALA)-mediated non-lethal sonodynamic therapy (NL-SDT) in macrophage-subset polarization and atherosclerotic lesion stability and explored the potential underlying mechanisms. Using Western diet-fed apolipoprotein E (apoE)(−/−) and green fluorescent protein (GFP)-positive bone marrow (BM) chimeric mouse models, we demonstrated that NL-SDT promoted phenotypic switching of both BM-derived and resident macrophages from M1 to M2 and significantly inhibited AS progression. Further mechanistic studies indicated that NL-SDT enhanced macrophage differentiation toward the M2 phenotype by activating the reactive oxygen species (ROS)–5′ AMP-activated protein kinase (AMPK)–mammalian target of rapamycin complex 1 (mTORC1)–autophagy signaling pathway in murine BM-derived M1 macrophages (BMDM1s). Moreover, NL-SDT drastically reduced lipid droplets, mainly by promoting apoAI-mediated cholesterol efflux in vitro. Specifically, administration of pharmacological inhibitors to the animal model showed a reciprocal effect on NL-SDT-induced macrophage polarization. These findings indicate that NL-SDT engages a virtuous cycle that enhances M1-to-M2 polarization, cholesterol efflux, and anti-inflammatory reactions in advanced plaque in vivo and in BMDM1s in vitro by activating the ROS–AMPK–mTORC1–autophagy pathway. This discovery might help elucidate the mechanism underlying NL-SDT as a potential treatment to prevent atherothrombotic events.